Peran promosi dan kualitas pelayanan pada keputusan konsumen di marketplace - Nendi, Ikhsan; Koesharijadi, Koesharijadi; Merthayasa, Anak Agung Alit (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study is to analyze the role of promotion and service quality on consumer decisions in the marketplace. The method used for the literature study approach, the data source comes from journals obtained through a google schoolar search and reference books related to this article. The results of this literature review are 1) the role of promotion as an effort that can be made by companies to be known and have an impact on choosing the goods and services offered. The role of a good promotion can have a positive impact on consumer decisions in determining the purchase of goods/services. 2) Service quality has an effect on product purchasing decisions. The quality of services offered by the company will lead to consumer loyalty to use the products produced by the company and besides that consumers get a good impression of the market making it possible to make repurchase decisions.